Preservation of Personal Care and Cosmetic Products: Effectiveness and Safety During the COVID-19 Pandemic - Correa, Gabriela [UNESP]; Canavez, Andrezza; Isaac, Vera [UNESP]; Lorencini, Marcio; Schuck, Desiree (My University, 2022)
The global beauty industry has been shocked by the COVID-19 pandemic. Currently, with increased hygiene habits, the choice of preservatives can be impacted by consumers opting for safe products. Products without preservation system could quickly become contaminated with mold, fungi, and bacteria, resulting in spoilage and increased risk of infection. This review explores the possible impacts of COVID-19 in the preservation of cosmetics from the perspective of effectiveness and safety. The preservatives included benzalkonium chloride, benzoic acid, sodium benzoate, benzyl alcohol, chloroxylenol, chlorphenesin, methylparaben, ethylparaben, propylparaben, butylparaben, phenoxyethanol, sorbic acid, potassium sorbate, as well as the multifunctional/ booster agents ethylhexylglycerin, caprylyl glycol, and natural antimicrobials. First, we highlight the current scenario of cosmetic preservation, the mode of action, and the maximum concentration allowed for preservatives; then examines overexposure to preservatives. Unexpectedly, the COVID-19 pandemic paralyzed the world market, and cosmetic industries had to adapt to a new reality. Due to the widespread use of cosmetic products, the prevalence of allergies, microbiological resistance, the need for proper prevention of product contamination, and concerns over the safety of preservatives, further investigations into the modes of action of traditional or alternative preservatives are needed to create successful safety products.